2017
DOI: 10.1186/s12964-017-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 interaction with active Smad2 modulates transforming growth factor-β regulated transcription

Abstract: BackgroundThe simplicity of Transforming Growth Factor ß (TGFβ) signaling pathway, linear and non-amplified, hardly sustains its variety of responses. This is often justified by the complex regulation showed by Smad proteins, TGFβ signaling intracellular transducers, object of post-translational modifications that modulate TGFβ-dependent transcription. Protein acetylation is emerging as a compelling mechanism affecting the activities of significant transcription factors, including p53, FOXO or NF-kB. Smad prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 75 publications
(125 reference statements)
0
18
0
Order By: Relevance
“…Although TRPC3 is well‐established to play a central role in transducing cardiac fibrosis signalling, the mechanisms underlying its signal transduction function remain poorly understood. To address this issue, researchers have identified SIRT1 as a modulator of the transcription of TGF‐β‐dependent genes, which participate in the process of fibrosis . In a preliminary experiment, we found that Hcy could increase the level of TRPC3; nevertheless, the protein level of SIRT1 was decreased (Figure A).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Although TRPC3 is well‐established to play a central role in transducing cardiac fibrosis signalling, the mechanisms underlying its signal transduction function remain poorly understood. To address this issue, researchers have identified SIRT1 as a modulator of the transcription of TGF‐β‐dependent genes, which participate in the process of fibrosis . In a preliminary experiment, we found that Hcy could increase the level of TRPC3; nevertheless, the protein level of SIRT1 was decreased (Figure A).…”
Section: Resultsmentioning
confidence: 90%
“…To address this issue, researchers have identified SIRT1 as a modulator of the transcription of TGF-β-dependent genes, which participate in the process of fibrosis. 21,22 In a preliminary experiment, we found that Hcy could increase the level of TRPC3; nevertheless, the protein level of SIRT1 was decreased ( Figure 5A). SIRT1 could be a potential TRPC3interacting partner, as both regulate the process of cardiac fibrosis in synergy.…”
Section: Sirt1 Is An Trpc3-interacting Partnermentioning
confidence: 87%
“…Moreover, co-receptor molecules with the ability to modulate and which bind to TβRs have been described [18]. Furthermore, downstream to TβRs activation, intracellular transduction of the signal shows, again, possibilities for modulation by means of post-translational modifications [19,20] or the regulation of protein levels of the factors participating on either Smad-reliant canonical signaling [21] or MAP-kinase-dependent non-canonical signaling [22]. In that sense, the aspects of TGF-β signaling intracellular transduction and the crosstalk with other pathways have been the subject of extensive reviews [23][24][25][26].…”
Section: Tgf-β Signaling: a Context Dependent Mechanismmentioning
confidence: 99%
“…Although TRPC3 is well established to play a central role in transducing cardiac fibrosis signalling [21] , the mechanisms underlying its signal transduction function still remain poorly understood, especially when TRPC3 also regulates TGF-ß. To address this issue, researchers have identified SIRT1 as a modulator of the transcription of TGF-ß-dependent genes, which participate in the process of fibrosis [22] . In a preliminary experiment, we found that Hcy could increase the level of TRPC3;…”
Section: Sirt1 Is An Trpc3-interacting Partnermentioning
confidence: 99%